Associations of NETs with inflammatory risk and clinical predictive value in large artery atherosclerosis stroke: a prospective cohort study - Li, Jiang; Liu, Lei; Zhang, Ruxu; Pan, Liqun; Tan, Juanying; Ou, Mingxin; Luo, Xiuju; Peng, Jun; Hu, Zhongyang (Frontiers in Immunology, 2024)
Background and objectiveNeutrophil extracellular traps (NETs) with inflammatory risk are important contributors to cardiovascular disease, but no definitive information is available in large artery atherosclerotic (LAA) stroke. This study aims to investigate the association between NETs with related inflammatory biomarkers and prognosis of LAA stroke in the Chinese population.MethodsA prospective study involving 145 LAA stroke cases and 121 healthy controls was conducted. Serum levels of MPO-DNA, PAD4, HMGB1, C1q, AIM2, ASC, Caspase-1, IL-1β, IL-6, and IL-8 were determined in all participants. The biomarkers were detected at three time points after stroke onset (24 hours: T1, 48 hours: T2, 7 days: T3) for LAA stroke patients and once for controls. Patients were followed up for 2 years after the ischemic event.ResultsThe serum MPO-DNA, PAD4, C1q, IL-1β, IL-6 and IL-8 reach their peak at 24 hours after stroke onset and show a decreasing trend during acute phase. MPO-DNA, AIM2 and IL-1β at baseline were associated with poor outcome at 3 months, further GMDR analysis revealed that the combination of MPO-DNA, AIM2 and IL-1β exert a synergistic effect on the prognosis of LAA stroke (OR: 8.75 95%CI (2.10-32.42)). For time-to-event analysis, MPO-DNA, Caspase-1 and IL-1β at baseline were predictors of MVEs after stroke (HR:4.04 (95%CI 1.28-12.70), 2.33 (95%CI 1.06-5.12) and 4.09 (95%CI 1.39-11.99), respectively).ConclusionsNETs and related inflammatory biomarkers at baseline predicted outcome at 3 months and late major vascular events following LAA stroke, supporting a rationale of randomized trials for targeted therapy directed at high-risk patients with elevated baseline NETs and related inflammatory biomarkers.